Acceptability and Practicality of the Turkish Translation of Pediatric Gait Arm Legs and Spine in Turkish Children - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Background The pediatric Gait, Arms, Leg, and Spine (pGALS) is a practical questionnaire for musculoskeletal (MSK) system evaluation in school-age children. Objective The aim of this study was to evaluate the acceptability/practicality of pGALS Turkish translation in Turkey (cross-sectional study). Methods The Turkish translation of pGALS was administered to children (4-18 years) who attended to the Pediatric Emergency Department of Hacettepe University, Ankara, Turkey, and the outpatient clinic of the Physical Therapy and Rehabilitation Department of Marmara University, Istanbul, Turkey, during 1 month in 2016. The demographics, complaints, final diagnoses, and pGALS parameters were noted. The acceptability of pGALS was evaluated using visual analog scale. Results Ninety-five patients (median age, 108 months; male/female, 1.1) were enrolled. Sixteen patients (16.8%) had MSK diagnosis, whereas 79 (83.2%) had non-MSK diagnoses. Musculoskeletal diagnoses were as follows: scoliosis (n = 4), metatarsus adductus (n = 4), soft tissue injury (n = 3), lumber disk herniation (n = 2), muscle spasm (n = 1), Achilles tendinitis (n = 1), and tibia torsion (n = 1). The sensitivity was 64.7%, and specificity was 89.7% for positive response to 1 or more pGALS screening questions to detect abnormal pGALS. The most sensitive question was pain question. The most common abnormal pGALS components were spine and posture. The sensitivity and specificity of pGALS for detecting MSK diagnosis were 93.7% and 97.4%, respectively. The median duration of pGALS examination was 4 minutes. Most patients/parents found the duration acceptable (94.7%/97.9%, respectively) and reported that pGALS caused little/no discomfort (97.9%/96.8%, respectively). Conclusion This is the first study showing the Turkish version of pGALS as a valid, acceptable, and practical screening test in Turkey.
Keywords: child; musculoskeletal; pGALS; screening; PGALS; VALIDATION; SCREEN; CARE